Ballistic behavior of high hardness perforated armor plates against 7.62 mm armor piercing projectile - EKİCİ, BÜLENT (ELSEVIER SCI LTD, 2014)
In this paper, some of the important defeating mechanisms of the high hardness perforated plates against 7.62 x 54 armor piercing ammunition were investigated. The experimental and numerical results identified three defeating mechanisms effective on perforated armor plates which are the asymmetric forces deviates the bullet from its incident trajectory, the bullet core fracture and the bullet core nose erosion. The initial tests were performed on the monolithic armor plates of 9 and 20 mm thickness to verify the fidelity of the simulation and material model parameters. The stochastic nature of the ballistic tests on perforated armor plates was analyzed based on the bullet impact zone with respect to holes. Various scenarios including without and with bullet failure models were further investigated to determine the mechanisms of the bullet failure. The agreement between numerical and experimental results had significantly increased with including the bullet failure criterion and the bullet nose erosion threshold into the simulation. As shown in results, good agreement between Ls-Dyna simulations and experimental data was achieved and the defeating mechanism of perforated plates was clearly demonstrated. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Perforated plates; Ballistic simulation; High hardness armor; Johnson-Cook material model; Armor piercing bullet; STEEL PLATES; RESISTANCE; IMPACT; HOLES